Antivaleria viridimacula - Rybalkin, Sergey A. (Zenodo, 2020)
Antivaleria viridimacula (Graeser, 1889) Fig. 1: 7 Material. Russia: Kunashir Island, 4.5 km NW Mendeleyevo Airport, Tretyakovo village, 14.09– 22.09.2019, 4 ex., leg. S. Rybalkin. Distribution. Russia (Khabarovsky Krai, Sakhalin, Primorsky Krai, Kuril Islands (Iturup Island), Japan (Hokkaido, Honshu, Shikoku, Kyushu), China, Korea, (Lelej 2016). The species is recorded for the first time from Kunashir Island. Published as part of Rybalkin, Sergey A., 2020, On the knowledge of Lepidoptera of Kunashir Island, Russia, pp. 98-105 in Amurian Zoological Journal XII (2) on page 99, DOI:10.33910/2686-9519-2020-12-2-98-105, http://zenodo.org/record/11362013